G20210A Prothrombin gene polymorphism and coronary ischaemic syndromes: a phenotype-specific meta-analysis of 12 034 subjects. Issue 1 (15th December 2003) - Burzotta, F; Paciaroni, K; De Stefano, V; Crea, F; Maseri, A; Leone, G; Andreotti, F
Abstract : Objective: To investigate the possible link between the G20210A prothrombin gene variant and different forms of ischaemic heart disease. Design: Phenotype-specific meta-analysis of 19 studies published within March 2002, globally including 4944 patients and 7090 controls. Sample size, inclusion criteria, geographical location, clinical presentation, age, cardiovascular risk factors, and angiographic extent of disease were extracted from each study. Analyses were done according to Mantel-Haenszel. Results: Overall, the odds ratio (OR) for unspecified ischaemic heart disease associated with the 20210A allele was 1.21 (95% confidence interval (CI) 0.99 to 1.59, n = 12 034). Similar findings were seen for acute coronary syndromes (unstable angina and myocardial infarction) and for myocardial infarction without age limits (OR 1.24, 95% CI 0.98 to 1.63, n = 10 240; and OR 1.19, 95% CI 0.93 to 1.58, n = 9765). The effects were similar in male and female subjects. In the 1931 subjects < 55 years of age, the OR for myocardial infarction increased to 1.77 (95% CI 1.16 to 3.42) and in the 1359 subjects < 45 years to 2.30 (95% CI 1.27 to 4.59). No significant association was found between the 20210A allele and the presence of angiographically documented coronary disease (OR 1.08, 95% CI 0.70 to 1.64, n = 3444). However, patients with 0/1 vessel disease at angiography showed a greater prevalence of the A allele than those with multivessel disease (relative risk 2.0, 95% CI 1.2 to 3.1, n = 2376). Conclusions: G20210A prothrombin gene polymorphism may represent a modest but significant risk factor for myocardial infarction at young ages and favour the expression of ischaemic heart disease among individuals who have a limited extent of coronary atherosclerosis at angiography.